BRAND LOYALTY WISATAWAN NUSANTARA TERHADAP BALI BERDASARKAN BRAND EXPERIENCE YANG DIMEDIASI BRAND TRUST DENGAN CHSE SEBAGAI VARIABEL MODERAS - I Made Bayu Wisnawa; I Nengah Aristana; I Wayan Edi Arsawan; Susila, I Made Gede Darma (Universitas Triatma Mulya, 2023)
The Covid-19 pandemic has caused the collapse of the tourism sector. The implementation of health protocols (CHSE) and vaccinations made the situation even better. Tourist loyalty to tourist destinations is the ultimate goal for every destination manager. At this time trust and experience are the most important variables in determining loyalty. This study aims to determine: i) the effect of brand experience on brand loyalty, ii) the effect of brand trust on brand loyalty, iii) the effect of brand trust on brand loyalty, iv) the role of brand trust in mediating the relationship between brand experience and brand loyalty, v) the role of the application of health protocols (CHSE) as a moderating variable. This study used a sample of 200 tourists visiting Bali. Data analysis was performed using Smart PLS. The results of the research are: i) brand experience has a positive and significant effect on brand loyalty, ii) brand experience has a positive and significant effect on brand trust, iii) brand trust has a positive and significant effect on brand loyalty iv) brand trust partially mediates the influence of brand experience on brand loyalty, v) CHSE moderates the effect of brand experience on brand loyalty, but does not moderate the effect of brand trust on brand loyalty. Keywords: brand loyalty, brand experience, brand trust, CHSE, Covid-19